ABI End of Initiative - 2024 Progress Deep Dive of the cassava breeding team from IITA - Rabbi, Ismail Y; Mbanjo, Gaby (International Institute of Tropical Agriculture, 2024)
The presentation summarizes the cassava breeding team's efforts and progress from 2022 to 2024 through a series of questions that highlight the team's breeding achievements. It also discusses the team's successes and challenges during this period.